Makna Sinkronik-Diakronik Pada Term Al-Qur’an dan al-Kitab Pendekatan Bahasa Syahrur: Synchronic and Diachronic Meaning on Term Al-Qur’an, al-Kitab and al-Dzikr (Syahrur’s Linguistic Approach) - Mia Fitriah El-Karimah (Universitas Ahmad Dahlan, 2022)
Syahrur introduced the term tsabat an-nash wa taghayyur al-muhtawa, which means that the text of the Qur'an is fixed, but the meaning of the text has changed so that it can be interpreted dynamically according to situation and context. He disassembled from etymology to morphology which can be seen in the redefinition of Al-Qur'an which is considered synonymous. This study uses a qualitative method with synchronous and diachronic analysis. This research is a literature study with al-Kitab wal-Qur'an and Qira'ah Muashirah written by Syahrur as primary data. The findings show that first; Syahrur used linguistics developed by two classical Arabic figures; Ibn Jinni's synchronic theory and al-Jurjani's diachronic theory. Second; the method related to synchronic and diachronic analysis was not fully carried out. Third, Syahrur conducted more semantic studies with syntagmatic-paradigm analysis with the intratextuality technique which Syahrur called manhaj al-tartil so that definitions of the mushaf emerged with the term al-kitab, with the addition of lam ta'rif to become al-kitab. Its meaning refers to the entire set of themes revealed to Muhammad SAW, while the Qur'an is a theme. So that the Qur'an is not identical with the Bible.